Pengaruh Pelaksanaan Pendidikan Karakter Berbasis Nilai-Nilai Islam dan Kemandirian Siswa Terhadap Prestasi Akademik di Sekolah Menengah Pertama Islam Berbasis Pesantren di SMP Modern Al Miftah - Ahmad Izzul Haq; Munirul Abidin (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This study aims to analyze the influence of character education based on Islamic values and student independence on academic achievement in the pesantren environment. This study uses a quantitative approach with a survey method involving 100 students of Al Miftah Modern Junior High School as a research sample. Data was collected through a Likert scale questionnaire that had been tested for validity and reliability. The validity test results showed that all questionnaire items were valid with a significance value of < 0.05, while the reliability test produced a Cronbach's Alpha score of 0.285 for character education and 0.388 for student independence. The results of regression analysis showed that character education and student independence partially had a significant influence on academic achievement, with t-values of 71.909 and 85.738 respectively (Sig. < 0.001). Simultaneously, these two variables also had a significant effect on academic achievement with an F value of 15097.182 (Sig. < 0.001). This study shows the importance of character education and student independence in supporting students' academic success in the pesantren environment. These results contribute to the development of the pesantren curriculum that emphasizes character formation and student independence.